Human Trafficking and the Human Rights Protection Crisis in East Nusa Tenggara, Indonesia - Semuel Haning; Agustin Leni Magdalen Rohi Riwu; Arnold J Sjah (Jurnal Ilmu Hukum Kyadiren, 2026)
Human rights challenges in East Nusa Tenggara (NTT), including human trafficking, the exploitation of migrant workers, conflicts concerning indigenous peoples’ rights, and the limited effectiveness of legal protection mechanisms, reflect a persistent gap between legal norms and their practical implementation. This study aims to analyze the similarities, differences, and shortcomings of the legal framework governing human rights protection in NTT, assess the urgency of legal reform, and formulate policy recommendations to enhance the effectiveness of human rights protection. The research employs a normative legal method with a comparative law approach, drawing upon statutory regulations, international human rights instruments, legal doctrines, and relevant scholarly literature. The findings indicate that national law, international human rights standards, and customary law share a common objective of safeguarding human dignity; however, they differ significantly in their protection mechanisms and dispute-resolution procedures. The study further identifies major weaknesses in legal enforcement, the harmonization of customary law with human rights principles, and institutional effectiveness. It concludes that comprehensive legal reform is required through regulatory strengthening, improved institutional coordination, expanded human rights education, and the harmonization of customary law with human rights norms to ensure more effective and sustainable human rights protection.